The American Jewish periphery: an overview - Joel Perlmann (Levy Economics Institute of Bard College, 2006)
This paper calls attention to the American Jewish peripheryAmericans of recent Jewish origin who have only the most tenuous connections, if any, with those origins. This periphery has been growing to the point that there are now, for example, nearly a million Americans with recent Jewish origins (origins no farther back in time than the nuclear family in which they were raised) who report that they are Christians. The paper focuses heavily on the National Jewish Population Survey (NJPS) of 2000. First, the dataset provides us an excellent dataset on Americans of recent Jewish origin. Second, it provides us with a great deal of information about the ethnocultural trajectories of those Americans, as shown in the social and cultural characteristics of NJPS respondents. Finally the paper considers some of the (sometimes bitter) discussions about the NJPS as a cultural phenomenon indicative of an ethnic group grappling with widespread intermarriage: specifically, the discussions about which NJPS respondents should be recognized as full-fledged Jews, and which should be thought of as having drifted too far to be so defined. I also draw on the experience of other ethnocultural groups for illumination as to how these groups have dealt with a legacy of widespread intermarriage.
Keywords: 330